Per se drugged driving laws and traffic fatalities - D. Mark Anderson; Daniel I. Rees (Institute for the Study of Labor (IZA), 2012)
The Office of National Drug Control Policy (ONDCP) recently announced a goal of reducing drugged driving by 10 percent within three years. In an effort to achieve this goal, ONDCP is encouraging all states to adopt per se drugged driving laws, which make it illegal to operate a motor vehicle with a controlled substance in the system. To date, 16 states have passed per se drugged driving laws, yet little is known about their effectiveness. The current study examines the relationship between these laws and traffic fatalities, the leading cause of death among Americans ages 5 through 34. Our results provide no evidence that per se drugged driving laws reduce traffic fatalities.
Keywords: I10; I18; 330; drugged driving; per se laws; traffic fatalities; marijuana; Straßenverkehrsrecht; Alkoholkonsum; Wirkungsanalyse; Straßenverkehrsunfall; USA